A surgeon assistant robot for selected urological disorders - Ng, Wan Sing. (2008)
A brief introduction to medical problems related to the prostate and treatment methods is given, as well as some notable robotic and computer assisted devices for surgery. The report dwells mainly on the use of ultrasound to provide image guidance for the robot to conduct a procedure called transurethral resection of the prostate (TURP). The robot holds the ultrasound probe, so that there is a common frame of reference between the imaging means and the resection means.